The Buss-Perry Aggression Questionnaire: construct validity and gender invarianceamong Argentinean adolescents - Cecilia Reyna (Universidad de San Buenaventura, 2011)
The Aggression Questionnaire (Buss & Perry, 1992) is one of the most used instruments to assess aggression; it includes 29 items grouped into 4 factors. Furthermore, a reduced version of 12-item has been proposed (Bryant & Smith, 2001), and it has also been examined by several researchers. Nevertheless, Latin-American samples have rarely been included. In this study, exploratory and confirmatory models were evaluated among a sample of adolescents from Cordoba, Argentina (N = 371). Moreover, internal consistency and gender invariance were examined. A 2-factor structure resulted in the exploratory analysis, while 2- and 4-factor (short and long versions) structures showed acceptable fits in confirmatory analysis. In general, internal consistency was acceptable, and gender invariance was supported. Implications and limitations are discussed.